What Are DPT Program Practices and Attitudes Related to Population Health, Prevention, Health Promotion, and Wellness? Results of a National Survey. Issue 1 (24th September 2020) - Rethorn, Zachary D; Maxwell, Jessica L; Bezner, Janet R; Davenport, Todd E; Bradford, Elissa H; Ingman, Mary Sue; Magnusson, Dawn M
Abstract: Objective: Noncommunicable diseases have increased in prevalence and are now responsible for the majority of the burden of disease. Aligning entry-level (professional) physical therapist education with these changing societal needs may position physical therapists to best address them. However, no comprehensive understanding of the practices and attitudes related to population health, prevention, health promotion, and wellness (PHPW) content among accredited US professional doctor of physical therapy (DPT) programs has been established. This study aims to identify practices and attitudes related to PHPW content among accredited US DPT programs. Methods: A mixed-methods cross-sectional design using an electronic survey was utilized. Program directors of each accredited DPT program were identified using an official Commission on Accreditation in Physical Therapy Education list and invited to ascertain the perceived importance of PHPW, describe the delivery of PHPW content, and identify factors that influence inclusion of PHPW content in US DPT programs. Results: Individuals from 49% of 208 invited programs responded. Nearly all programs reported teaching prevention (96.1%), health promotion (95.1%), and wellness content (98.0%), while fewer reported teaching population health (78.4%). However, only 15% of PHPW topics were covered in depth. Facilitators and barriers to the delivery of PHPW content were reciprocal and included faculty with PHPW expertise, logistical flexibility and support, and the perceived importance of PHPW content. Conclusions: The majority of US DPT programs are teaching PHPW content. Lack of trained faculty and lack of professional competencies hinder further integration of PHPW content into curricula. Impact: The findings of this study highlight avenues for additional research to determine professional PHPW competencies and additional educational needs for faculty members.